The delusion of an education without values - Expósito, Cristián David (2020)
The school is the real and concrete space where those values traced in the curricular design of each educational system crystallize. It is here that there should also be a reflexive interaction that questions the citizen about the current cultural customs and those social and personal values more convenient to promote the welfare of the community. This entails the responsibility of raising adjustments to improve coexistence in society without compromising one's cultural roots. The delicate balance between these variables will produce harmony; otherwise, we will obtain a crisis that will generate antagonistic positions and in the place of peace we will only find a social gap. In this article we will address the deep relationship between the triad "education, values and ideology"; since every school situation, whatever the ideological position assumed, will be impregnated with certain values that impact on the education of people by the way they are conceived and incorporated into the curriculum.